Male mate choice in a sexually cannibalistic widow spider. (March 2018) - Waner, Shevy; Motro, Uzi; Lubin, Yael; Harari, Ally R.
Abstract : Males of the brown widow spider, Latrodectus geometricus (Theridiidae), invest energy in courtship displays and are often cannibalized after mating; accordingly, partial sex role reversal is expected. In this species, subadult females are able to mate and produce viable offspring. In contrast to mature females, these subadult females do not cannibalize their mates after copulation. Nevertheless, when given a choice, males preferred mature over subadult females and older over young mature females. We found no benefit for males in mating with the females of their choice. Older females were significantly less fecund than young mature females, and were not more fecund than subadult females. We tested possible advantages in mating with cannibalistic (mature) females, such as an increased probability of plugging the female's genital duct or longer copulations, or disadvantages in mating with subadult females, such as higher remating risk. None of these explanations was supported. Thus, we lack an adaptive explanation for male preference for mature older females. We suggest that older females produce more pheromone to attract males and that males are thus misled into mating with older, more aggressive and less fecund females. Highlights: Male brown widow spiders invest much energy in courtship, and risk cannibalism. By mating with subadult females, males save energy and avoid cannibalism. If mated, subadult females are fertile, but males avoided mating with subadults. Instead, males chose older adult females, despite not gaining any benefit.